2020
DOI: 10.21203/rs.2.17852/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Point-of-Care Ultrasound May Be Useful for Detecting Pediatric Intussusception at an Early Stage

Abstract: Background: This study aimed to verify the usefulness of point-of-care ultrasound (POCUS) performed by pediatric emergency physicians for detecting intussusception at an early stage. Methods: This retrospective study included 1-month- to 6-year-old children with clinically suspected intussusception, who underwent POCUS in the pediatric emergency department between December 2016 and February 2018. The criteria for performing POCUS were set to broader standards: presenting any one of intermittent abdominal pain/… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As interest in using POCUS continues to grow within pediatric EDs, it is important to develop evidence-based implementation strategies that improve patient outcomes without compromising safety. Recent research has focused on the use of POCUS for intussusception and has shown that POCUS has high sensitivity, specificity, and diagnostic accuracy for this application when compared with RADUS 4–6,9,21–26 . The use of POCUS for the evaluation of intussusception has several potential benefits to patients, including improvement of patient throughput in the ED, focusing the need for further diagnostic testing, and informing decisions regarding transfer from general to pediatric centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As interest in using POCUS continues to grow within pediatric EDs, it is important to develop evidence-based implementation strategies that improve patient outcomes without compromising safety. Recent research has focused on the use of POCUS for intussusception and has shown that POCUS has high sensitivity, specificity, and diagnostic accuracy for this application when compared with RADUS 4–6,9,21–26 . The use of POCUS for the evaluation of intussusception has several potential benefits to patients, including improvement of patient throughput in the ED, focusing the need for further diagnostic testing, and informing decisions regarding transfer from general to pediatric centers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has focused on the use of POCUS for intussusception and has shown that POCUS has high sensitivity, specificity, and diagnostic accuracy for this application when compared with RADUS. [4][5][6]9,[21][22][23][24][25][26] The use of POCUS for the evaluation of intussusception has several potential benefits to patients, including improvement of patient throughput in the ED, focusing the need for further diagnostic testing, and informing decisions regarding transfer from general to pediatric centers. In one recent multicenter study, 38% of children transferred from an outside hospital had a negative intussusception evaluation at the receiving hospital, suggesting that these transfers may have been avoidable assuming there were no other indications for transfer.…”
Section: Discussionmentioning
confidence: 99%
“…2) Although point-of-care USG by trained pediatric emergency physicians had high sensitivity (100%) and specificity (95.6%), 3) abdominal USG is usually performed by a radiologist rather than a pediatrician or emergency physician because most pediatric intussusception is managed in training hospitals in Korea. 4) The advantage of performing USG by radiologists is that other findings can determine the failure of enema reduction, 5) including the blood supply status of the intussusception, presence of intestinal necrosis or ascites, and the pathologic leading causes can also be confirmed.…”
mentioning
confidence: 99%